Developing the immunologybook for animal and human physiology subject - Zuni Mitasari; Abdul Gofur (JPBI (Jurnal Pendidikan Biologi Indonesia), 2017)
The objective of the study was to develop an immunology book for Animal and Human Physiology subject. This book was developed based on the Thiagarajan development model which was modified of: Define, Design, Develop, dan Disseminate (4D). The data expert validation instrument was questionnaire using Likert scales, comments, and recommendation sheets. Expert appraisal was done by  material expert and media and design learning expert. The developmental testing was conducted using questionnaire to test the readibility.  The  expert validation was conducted by material expert as well as design and media learning expert validator; meanwhile, the field test was done to measure the  readability. The validity test results were: the material expert state that the material is valid (97.14%), as well as the design and learning media expert (84.88%) and field test by students (88.17%).